Análise do princípio da atipicidade do ilícito administrativo disciplinar à luz do princípio do devido processo legal substantivo - Dezan, Sandro Lucio (2007)
The present study searches the analysis of the juridical effects produced by the legality principles and of the just substantive legal process, in the definition of primary precepts of disciplinary administrative illicit actions, giving emphasis to the functionalism of the descriptive type of illicit conduct and, this way, serving of ‘ lege ferenda’ , to the interpretation, to the application and the definition of the public servants fundamental rights in relation to the infraconstitutional law. In fact, it points to the invalidity of the indeterminated types, existents in the federal public services statutes, declining that the principle of atypical ness settled by national and foreign authorized doctrine as a regent of the federal juridical sanctioned system, it doesn’t receive validity foundation from the constitutional principles of guarantee. Thus,the penal law principles are verified, constitutionalist qualified and attached to the guarantees of the application of a right and just Law restrictive of the limitlessness of the state’s ‘Jus puniendi’ with the modern guardianship of the fundamental rights to provide with foundation in the clauses of constitutional opening, full application, to the referred juridical administrative discipline, refuting the vague types, opened, indeterminated, extinguisher of violations in the juridical system in comment. As a natural consequence of this analysis it gauges a general theory of sanctioned guarantor law, validy for all grain fields of illicit that involves juridical relations to the public Law. On the sight of this positioning is inevitable the analysis of the penal law theories, when the transposition to the federal law sanctioned, once that they reflect in some cases, in several manners in these law branches, as for instance in what refers to the subjective imputation of the illicit and to the ‘conatus’ (trying of the illicit ), that sometimes are applicable and, other times don’t have applicability, in proportion that they are put in one or in another branch.